PENGARUH BRAND AWARENESS DAN CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN - Nur Jihana,; Erni Yuningsih,; Yulianingsih, (Jurnal Visionida, 2024)
This study aims to test and analyse the effect of brand awareness and celebrity endorsement on purchasing decisions with consumer confidence as an intervening variable. The population in this study were consumers of Arei products in Bogor City, consisting of 5476 people. Sampling amounted to 100 people using the sample calculation with the Yamane formula. Data analysis uses descriptive and verification analysis, as well as using path analysis and Sobel Test analysis for intervening variables. The results showed that brand awareness and celebrity endorsement have a direct, positive and significant effect on consumer trust. Brand awareness, celebrity endorsement and consumer confidence have a direct, positive and significant effect on purchasing decisions. Brand awareness and celebrity endorsement have an indirect, positive and significant effect on purchasing decisions.